Factors Related to Carpal Tunnel Syndrome Complaints among Computer Operators - Zainuddin, Asnia; Magvira, Devi Ayu; Saptaputra, Syawal Kamiluddin (GLOBAL HEALTH SCIENCE GROUP, 2024)
The use of static electronic devices for a long time, especially computers, can affect the musculoskeletal system of office workers due to incorrect hand positions when using a mouse or keyboard and repetitive work. Computer operators at PT. X can spend time working in front of a computer for around 7-8 hours a day, even if they are facing a work deadline, they can spend more than 12 hours working in front of a computer. In general, the body part that is used most often in doing work is the hand where the fingers are repeatedly used for a long period of time when pressing keyboard buttons and operating the mouse. This has the potential to cause Carpal Tunnel Syndrome (CTS) complaints. This study aims to determine the relationship between work period, length of work, and awkward hand positions with Carpal Tunnel Syndrome (CTS) complaints in computer operators at PT. X, Kendari City. The design of this study is cross-sectional. The sampling technique uses total sampling where the sample is all 35 computer operators. A questionnaire is used to determine the characteristics of the respondents. To determine the awkward position of the hand while working, an observation sheet is used. Phalen's test is a test performed to identify if there is CTS in workers. Based on the results of bivariate analysis, it is known that the length of service is related to CTS complaints with a p value = 0.005. Length of service is related to CTS complaints with a p value = 0.004). Awkward hand positions are related to Carpal Tunnel Syndrome complaints with a p value = 0.001. In this study, it was found that the variables that had a relationship with CTS complaints in computer operators at PT. X, Kendari City were work period, length of work, and awkward hand positions were factors.